Analytical weight estimation of landing gear designs. (October 2017) - Munjulury, RC; Berry, P; Borhani Coca, D; Parés Prat, A; Krus, P
Landing gear weight calculations can be carried out using statistical or analytical methods. Statistical methods were used in the past and offered quick group weights. However, they are not capable of computing accurately the weight of landing gears, which have special geometries and performance. In this work, landing gear weight is computed using analytical methods based on parametric 3D models. The procedure established by Kraus and Wille is applied as a baseline so as to create a procedure capable of dealing with landing gear weight calculations. This method is designed to be as flexible as possible, giving the user the freedom to modify many options and parameters and integrate landing gear design into Robust Aircraft Parametric Interactive Design.